On identifiability of mixtures of independent distribution laws∗∗∗∗∗∗. (1st July 2014) - Kovtun, Mikhail; Akushevich, Igor; Yashin, Anatoliy
<x content-type="archive" xml:space="preserve">Abstract</x> We consider representations of a joint distribution law of a family of categorical random variables (i.e., a multivariate categorical variable) as a mixture of independent distribution laws (i.e. distribution laws according to which random variables are mutually independent). For infinite families of random variables, we describe a class of mixtures with identifiable mixing measure. This class is interesting from a practical point of view as well, as its structure clarifies principles of selecting a â€œgoodâ€ finite family of random variables to be used in applied research. For finite families of random variables, the mixing measure is never identifiable; however, it always possesses a number of identifiable invariants, which provide substantial information regarding the distribution under consideration.